2020
DOI: 10.1186/s13054-020-2830-x
|View full text |Cite
|
Sign up to set email alerts
|

Monocytic HLA-DR expression kinetics in septic shock patients with different pathogens, sites of infection and adverse outcomes

Abstract: Background: Decreased monocytic (m)HLA-DR expression is the most studied biomarker of sepsis-induced immunosuppression. To date, little is known about the relationship between sepsis characteristics, such as the site of infection, causative pathogen, or severity of disease, and mHLA-DR expression kinetics. Methods: We evaluated mHLA-DR expression kinetics in 241 septic shock patients with different primary sites of infection and pathogens. Furthermore, we used unsupervised clustering analysis to identify mHLA-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
76
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 83 publications
(92 citation statements)
references
References 29 publications
6
76
0
2
Order By: Relevance
“…Invasive candida infection commonly appears in highly immunosuppressed patients and lower value of mHLA-DR could be associated with higher risk of ICI. Continuing or declining immune de ciency is associated with an increased mortality [32]. Similarly, our results suggest an increased probability of ICI when mHLA-DR remains < 5000 Ab/c after day 7 of septic shock.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…Invasive candida infection commonly appears in highly immunosuppressed patients and lower value of mHLA-DR could be associated with higher risk of ICI. Continuing or declining immune de ciency is associated with an increased mortality [32]. Similarly, our results suggest an increased probability of ICI when mHLA-DR remains < 5000 Ab/c after day 7 of septic shock.…”
Section: Resultssupporting
confidence: 70%
“…Our population is mainly patients with sepsis related to peritonitis. Leijte et al found median mHLA-DR over 6000 Ab/c in bacterial peritonitis [32]. Invasive candida infection commonly appears in highly immunosuppressed patients and lower value of mHLA-DR could be associated with higher risk of ICI.…”
Section: Resultsmentioning
confidence: 99%
“…Although mHLA-DR expression levels in COVID-19 patients were lower than those observed in healthy subjects (15,000-45,000 mAb/cell [5]), the extent of suppression was less pronounced than observed in bacterial septic shock patients (geometric mean [95% CI] of 11,860 [11,035-12,746] vs. 5211 [4904-5537] mAb/cell, respectively; p < 0.0001; Fig. 1a, sepsis data from [1]). mHLA-DR expression kinetics revealed no change over time (Fig.…”
mentioning
confidence: 86%
“…Fig. 1 a mHLA-DR expression in patients with COVID-19 (n = 24, multiple timepoints) and bacterial septic shock (n = 241, days 1-2, 3-4, and/or 6-8 after onset of septic shock, obtained using the same methodology, data recently published [1]). Horizontal line indicates geometric mean.…”
mentioning
confidence: 94%
See 1 more Smart Citation